Effect of stator geometry of impact pulverizer on its grinding performance. (27th January 2015) - Nakamura, Hideya; Kan, Hiroyuki; Takeuchi, Hirohisa; Watano, Satoru
Abstract: An impact pulverizer is widely employed for dry milling of powders in many industrial sectors. However, effect of the equipment geometry on grinding performance of the impact pulverizer is still unknown. This paper presents systematic analysis of effect of the stator geometry of an impact pulverizer on its grinding performance. Three types of stators with different concave angles were investigated. Effect of the stator concave angles on grinding performance of the impact pulverizer was investigated through both experimental and theoretical approaches. As the theoretical approach, a computational fluid dynamics (CFD)–discrete phase model (DPM) coupling simulation was conducted and the particle–stator collision properties were analyzed. The grinding experiment demonstrated that size of the ground powder was reduced with a use of stator with smaller concave angle. A CFD–DPM simulation revealed that the cumulative impact energy per particle became higher at smaller concave angle, because stator with smaller concave angle lead to longer particle residence time and higher total number of the particle–stator collision. In summary, this work revealed effect of the stator geometry on grinding performance of the impact pulverizer; the stator concave angle mainly affects the particle residence time and total number of the particle–stator collision. This results in change in the cumulative impact energy, leading to change in grinding performance of the impact pulverizer. Highlights: Effect of stator geometry on performance of an impact pulverizer was investigated. Size of the ground powder was clearly influenced by the stator geometry. Particle–stator collision at various stator geometries was analyzed by CFD–DPM.